Palliative treatment of malignant gastroduodenal obstruction: Applications of self-expandable metal stent - Işılay NADİR; Erkan Parlak; Fahrettin KÜÇÜKAY; Selçuk Dişibeyaz; Bahattin ÇİÇEK; Yasemin ÖZİN; Sedef ÖZDAL KURAN; Nurgül Şaşmaz; Turhan CUMHUR; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-